Robust optimization and its applications in cognitive radio networks. - Gong, Shimin. (2013)
An optimal design of the cognitive radio may not operate properly due to unexpected fluctuations of system parameters in non-ideal working environment. Among various uncertain factors, the most notorious factor is the fluctuation of channel gain due to the stochastic nature of wireless channels. In our research, we try to propose a new framework that brings uncertainty into the analysis and design of a practical system. As a demonstration, we apply this framework to study two major aspects of the cognitive radio networks, i.e., spectrum identification and exploitation.